An experimental evaluation of the antidiabetic and antilipidemic properties of a standardized Momordica charantia fruit extract - Naik Suresh R; Panda Vandana S; Lagishetty Chakradhar V; Fernandes Nafisa PC (BMC, 2007)
Abstract Background The MCE, Momordica charantia fruit extract Linn. (Cucurbitaceae) have been documented to elicit hypoglycemic activity on various occasions. However, due to lack of standardization of these extracts, their efficacy remains questionable. The present study was undertaken by selecting a well standardised MCE. This study reports hypoglycemic and antilipidemic activities of MCE employing relevant animal models and in vitro methods. Methods Diabetes was induced in Wistar rats by a s.c., subcutaneous injection of alloxan monohydrate (100 mg/kg) in acetate buffer (pH 4.5). MCE and glibenclamide were administered orally to alloxan diabetic rats at doses of 150 mg/kg, 300 mg/kg & 600 mg/kg, and 4 mg/kg respectively for 30 days, blood was withdrawn for glucose determination on 0, 7, 14, 21 and 30th days. On the 31st day, overnight fasted rats were sacrificed and blood was collected for various biochemical estimations including glycosylated haemoglobin, mean blood glucose, serum insulin, cholesterol, triglcerides, protein and glycogen content of liver. The hemidiaphragms and livers were also isolated, carefully excised and placed immediately in ice cooled perfusion solution and processed to study the glucose uptake/transfer processes. Hypolipidemic activity in old obese rats was evaluated by treating two groups with MCE (150 mg/kg & 300 mg/kg) orally for 30 days and determining total cholesterol, triglyceride and HDL-CH, LDL-CH and VLDL-CH levels from serum samples. Results Subchronic study of MCE in alloxan induced diabetic rats showed significant antihyperglycemic activity by lowering blood glucose and GHb%, percent glycosylated haemoglobin. Pattern of glucose tolerance curve was also altered significantly. MCE treatment enhanced uptake of glucose by hemidiaphragm and inhibited glycogenolysis in liver slices in vitro. A significant reduction in the serum cholesterol and glyceride levels of obese rats following MCE treatment was also observed. Conclusion Our experimental findings with respect to the mechanism of action of MCE in alloxan diabetic rats suggest that it enhances insulin secretion by the islets of Langerhans, reduces glycogenesis in liver tissue, enhances peripheral glucose utilisation and increases serum protein levels. Furthermore, MCE treatment restores the altered histological architecture of the islets of Langerhans. Hence, the biochemical, pharmacological and histopathological profiles of MCE clearly indicate its potential antidiabetic activity and other beneficial effects in amelioration of diabetes associated complications. Further, an evaluation of its antilipidemic activity in old obese rats demonstrated significant lowering of cholesterol and triglyceride levels while elevating HDL-cholesterol levels. Also, the extract lowered serum lipids in alloxan diabetic rats, suggesting its usefulness in controlling metabolic alterations associated with diabetes.